PENTASHIHAN BUKU YASIN SEBAGAI UPAYA PEMELIHARAAN OTENTISITAS Al-QURÃN (KASUS MASYARAKAT WAYDADI SUKARAME BANDAR LAMPUNG) - Jayusman, Jayusman, (P3M STAIN Jurai Siwo Metro, 2011)
This research will examine further correct Yasin books that circulated in the community, knowing the errors of Yasin books that circulating and give solutions that can be attempted to restrict the circulation of Yasin books that are not corrected. The methodology used in this study are : field descriptive research, using a normative approach, studies is ulum al-Quran. The population in this study are all Yasin books that circulated in the community at Waydadi village, District Sukarame, Bandarlampung. Sampling using a non probality sampling. Collecting data in this study using the documentation techniques and than analyzed by qualitative approach. Conclusion done inductively. The findings of this research is the Yasin books that circulated in the Waydadi community , Sukarame Bandar Lampung not be corrected or ditashih by the competent authorities - in this case Lajnah Pentashih al-Quran Ministry of Religious Affairs. Error of Yasin books that circulating in the community, consists of letter errors, harakat errors, technical errors of writing, and inconsistencies in the writing. Solutions that can be attempted restrict of the circulation of Yasin books that are not corrected in society is synergy among Lajnah Pentashih al-Quran as the institution that is authorized by the Government, authors, publishers and each individual Muslim that have dedicated and committed to preserve and maintain the authenticity al-Quran.Keywords: Authenticity, the Quran, Tashih, Yasin Books